2008
DOI: 10.4172/plastic-surgery.1000586
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of congenital constriction band syndrome in children: Replacing Z-plasty with direct closure

Abstract: Congenital constriction band syndrome is a sporadic condition that may also be present in association with other congenital anomalies. It has an incidence varying from one in 1200 to one in 15,000 live births. There is a significant predilection for the upper extremities and distal limbs. The two main objectives for the treatment of congenital constriction band syndrome are improvement of function and improvement of cosmetic appearance. Different surgical techniques, such as Z-plasty, have been described and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 12 publications
0
12
0
3
Order By: Relevance
“…No Brasil, Costa et al 7 publicaram uma série de 16 casos com acometimento do membro inferior associado a pé torto congênito, e Pardini et al 1 As controvérsias giram em torno da realização da ressecção em um ou mais tempos cirúrgicos. Os trabalhos mais antigos defendem a ressecção em dois ou mais tempos cirúrgicos 12 , enquanto as publicações mais recentes defendem que ela ocorra em um único tempo cirúrgico 1,7 . Não há, portanto, um estudo com relevância significativa que indique um tratamento em detrimento do outro.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…No Brasil, Costa et al 7 publicaram uma série de 16 casos com acometimento do membro inferior associado a pé torto congênito, e Pardini et al 1 As controvérsias giram em torno da realização da ressecção em um ou mais tempos cirúrgicos. Os trabalhos mais antigos defendem a ressecção em dois ou mais tempos cirúrgicos 12 , enquanto as publicações mais recentes defendem que ela ocorra em um único tempo cirúrgico 1,7 . Não há, portanto, um estudo com relevância significativa que indique um tratamento em detrimento do outro.…”
Section: Discussionunclassified
“…O paciente que apresenta duas bandas em um mesmo membro deve ser conduzido com a ressecção da banda de constrição proximal, primeiramente, e após 60 a 120 dias, com ressecção da distal 1,7 . Havendo deformidades associadas nos pés, o tratamento cirúrgico convencional dessa deformidade deve ser realizado após um período mínimo de 90 dias 7,12 , sendo possíveis maus resultados com a inversão da sequência do tratamento.…”
Section: Publicaram Outro Estudo Comunclassified
“…Basado en esta premisa, no habría ningún riesgo en la liberación de la brida en un sólo tiempo quirúrgico 5,6 . Es más, la liberación de la brida constrictiva en sí facilita el retorno venoso y linfático disminuyendo el edema, lo que mejora la irrigación del tejido distal a la constricción así como a la piel subyacente.…”
Section: Discussionunclassified
“…Choulakian and Williams presented two cases of linear closure without Z-plasty in the extremities. 10 Habenicht et al reported 43 extremity constriction rings treated with circumferential excision and linear skin closure. 11 Recurrent constriction was not observed over an average follow-up of 6.5 years.…”
mentioning
confidence: 98%